2019
DOI: 10.3389/fmicb.2018.03205
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Trypanocidal Activity, Genomic Analysis of Isolates, and in vivo Transcription of Type VI Secretion System of Serratia marcescens Belonging to the Microbiota of Rhodnius prolixus Digestive Tract

Abstract: Serratia marcescens is a bacterium with the ability to colonize several niches, including some eukaryotic hosts. S. marcescens have been recently found in the gut of hematophagous insects that act as parasite vectors, such as Anopheles, Rhodnius, and Triatoma. While some S. marcescens strains have been reported as symbiotic or pathogenic to other insects, the role of S. marcescens populations from the gut microbiota of Rhodnius prolixus, a vector of Chagas’ disease, remains unknown. Bacterial colonies from R. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 102 publications
0
17
0
1
Order By: Relevance
“…In this sense, the gut bacterial microbiota impacts the development of trypanosomatids in insects [17][18][19]. In R. prolixus, the intestinal microbiota components identified to date are Serratia, Dietzia, Gordonia, Mycobacterium, Corynebacterium, Rhodococcus, Pectobacterium, and Staphylococcus [17,[20][21][22][23][24]. However, knowledge of the interaction between the triatomine and the T. cruzi with the bacterial species Rhodococcus rhodnii and Serratia marcescens is still scarce [17,18,23].…”
Section: Of 17mentioning
confidence: 99%
“…In this sense, the gut bacterial microbiota impacts the development of trypanosomatids in insects [17][18][19]. In R. prolixus, the intestinal microbiota components identified to date are Serratia, Dietzia, Gordonia, Mycobacterium, Corynebacterium, Rhodococcus, Pectobacterium, and Staphylococcus [17,[20][21][22][23][24]. However, knowledge of the interaction between the triatomine and the T. cruzi with the bacterial species Rhodococcus rhodnii and Serratia marcescens is still scarce [17,18,23].…”
Section: Of 17mentioning
confidence: 99%
“…The numbers of T. cruzi in aposymbiotic insects are ten times higher than in insects with a normal microbiota [247]. Some strains of Serratia marcescens, have direct trypanolytic activity [192,247,256,257], but this again only affects some T. cruzi strains as S. marcescens has been found in wild caught triatomines infected with T. cruzi [234,242,244,258]. Furthermore, in feral triatomines naturally infected with T. cruzi, there is an overrepresentation and subrepresentation of some Actinomycetes and Proteobacteria, but whether this helps or hinders T. cruzi infections remains to be addressed [234,241,245].…”
Section: Effects Of Trypanosomes On the Microbiotamentioning
confidence: 99%
“…marcescens has been found in wild caught triatomines infected with T . cruzi [ 234 , 242 , 244 , 258 ]. Furthermore, in feral triatomines naturally infected with T .…”
Section: Triatomine Symbiosesmentioning
confidence: 99%
“…Serratia marcescens , is a Gram-negative bacteria that compose R. prolixus microbiota ( Azambuja et al, 2004 ; Vieira et al, 2016 ). Recently, it was identified that S. marcescens strains from R. prolixus gut presented many virulence factors ( da Mota et al, 2019 ), as already described in other S. marcescens strains, including pore-forming toxins, such as hemolysins, which potentially cause damages to epithelial cells ( Hertle, 2000 , 2005 ; Ochieng et al, 2014 ; Lee et al, 2016 ). In D. melanogaster , it has been shown that S. marcescens infection induces gut damage and inflammatory reactions ( Lee et al, 2016 ).…”
Section: Discussionmentioning
confidence: 92%